Daya Dukung Tanah Pasir Dengan Perkuatan Geotekstil Tipe UW 150 Terhadap Variasi Lebar Fondasi dan Perkuatan - Cristina, V.I.; Martini, Martini (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2021)
Sand are soils that have low bearing capacity and are more affected by density. Therefore it is necessary to improve sand soil to increase the bearing capacity of the soil. One method of soil mechanical improvement is by inserting a sheet of reinforcement (geotextile) on the sand. The purpose of this research is to study the relationship of width of foundation (B) and width of reinforcement (Br) in increasing the support capacity of sandy soil and to know soil bearing capacity of sand at condition without and with reinforcement.The purpose of this research to know the modeling on sand in a test tub madeby steel plate with size 80cm x 80cm with a shallow foundation model measuring 8 cm x 8 cm, 10 cm x 10 cm and 12 cm x 12 cm. Loading is given by using a hydraulic jack. The soil is formed with a 50% relative density with the width of reinforcement (Br) inserted were 4B, 5B and 6B with the depth (u) 0.5B, spacing (z) 0.25B and a 3-sheet reinforecment (N)), where B is the width Foundation. Furthermore, it is determined the bearing capacity of the limit and the ratio of its bearing capacity (BCR).The result shows that giving the geotextile sheet on sand soil can increase the bearing capacity against the condition without reinforcement. Bearing capacity increases as the width of the foundation (B) is wider and the width of reinforcement (Br) or geotextile is wider. Based on the Tangent Intersection Method theory, the largest bearing capacity obtained at the width of the foundation (B) 12cm x 12cm and the reinforcing width (Br) 6B is 153 kN/m2 with 2.06 of the bearing capacity ratio. For the vesic theory, the largest bearing capacity obtained at the width of the foundation (B) 12cm x 12cm 274kN/m2 for the width of the 6B reinforcement with 3.32 of the bearing capacity ratio (BCR).